2017
DOI: 10.1111/bcpt.12835
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics of Enalapril in Relation to CES1 Genotype in Healthy Danish Volunteers

Abstract: This study investigated the influence of variations in the carboxylesterase 1 gene (CES1) on the pharmacokinetics of enalapril. Forty-three healthy, Danish, Caucasian volunteers representing different pre-defined genotypes each received 10 mg of enalapril. At specified time-points, plasma concentrations of enalapril and the active metabolite enalaprilat were measured. The volunteers were divided into six different groups according to their genetic profile of CES1: group 1 (control group, n = 16) with two CES1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“… 11 , 12 , 15 , 18 , 19 , 21 , 22 However, the clinical impact of the G143E variant differed significantly among drugs metabolized by CES1. For instance, this single‐nucleotide polymorphism (SNP) significantly altered the PKs and PDs of the CES1 substrate medications methylphenidate, 20 , 24 oseltamivir, 22 , 25 and clopidogrel 21 , 26 ; however, it had much less potent effect on the activation of the ACE inhibitor prodrugs enalapril, 28 quinapril, 27 and trandolapril, as we reported in this investigation. Of note, these studies utilized healthy volunteers with similar study designs and sample sizes.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“… 11 , 12 , 15 , 18 , 19 , 21 , 22 However, the clinical impact of the G143E variant differed significantly among drugs metabolized by CES1. For instance, this single‐nucleotide polymorphism (SNP) significantly altered the PKs and PDs of the CES1 substrate medications methylphenidate, 20 , 24 oseltamivir, 22 , 25 and clopidogrel 21 , 26 ; however, it had much less potent effect on the activation of the ACE inhibitor prodrugs enalapril, 28 quinapril, 27 and trandolapril, as we reported in this investigation. Of note, these studies utilized healthy volunteers with similar study designs and sample sizes.…”
Section: Discussionsupporting
confidence: 52%
“…The clinical relevance of CES1 genetic polymorphisms has been well‐documented for various CES1 substrate medications 23–26,28,34 . A previous in vitro study has demonstrated that trandolapril is selectively activated by CES1 in the human liver, and the CES1 variants, G143E and D260fs, completely impaired trandolapril activation in s9 fractions prepared from cells transfected with the variants 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enalapril is a prodrug which is hydrolyzed by carboxylesterase 1 (CES1) to form the active metabolite, enalaprilat (Ulm et al, 1982). It has been shown that polymorphism of CES1 affects the pharmacokinetics and pharmacodynamics of enalapril in human subjects (Tarkiainen et al, 2015;Stage et al, 2017). Enalapril is rapidly absorbed with about 40% of the dose (10 mg) converted to enalaprilat (Ulm et al, 1982).…”
Section: Introductionmentioning
confidence: 99%